2019
DOI: 10.1039/c9ra00522f
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of 4-methylcoumarins by cambial meristematic cells of Camptotheca acuminata

Abstract: Cambial meristematic cell (CMC) suspension cultures were investigated as a new biotransformation system for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The cultures of stem cell lines with a very high proportion of stem cells were established in this way. Until now, stem cell cultures have been established exclusively from isolated and cultured innately undifferentiated cambial meristematic cells from stem segments [22,[29][30][31][32][33]. However, the use of cambial meristematic cells from stem explants may not be the only way to establish an in vitro culture of stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cultures of stem cell lines with a very high proportion of stem cells were established in this way. Until now, stem cell cultures have been established exclusively from isolated and cultured innately undifferentiated cambial meristematic cells from stem segments [22,[29][30][31][32][33]. However, the use of cambial meristematic cells from stem explants may not be the only way to establish an in vitro culture of stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies on CMCs have been reported, but only in a limited number of plant species, mainly medicinal ones, e.g., Taxus cuspidata , Ginkgo biloba , Solanum lycopersicon 22 , Panax ginseng 22 , 28 , Catharanthus roseus 29 , Tripterygium wilfordii 30 , Camptotheca acuminate 31 , Ocimum basilicum 32 , Fraxinus mandshurica 33 . However, no study has been presented on the establishment and cultivation of stem cell or stem-like cell suspension cultures derived from Calendula officinalis L. Establishment of stem cell cultures in small volumes or in bioreactors should ensure higher production of cells and secondary metabolites in comparison with the cultivation of dedifferentiated cells in suspension cultures.…”
Section: Introductionmentioning
confidence: 99%